Towards the big data and digital evidences integrity / Shekh Abdullah-Al-Musa Ahmed, Nik Zulkarnaen Khidzir and Tan Tse Guan - Ahmed, Shekh Abdullah-; Khidzir, Nik Zulkarnaen; Tan, Tse Guan (Universiti Teknologi MARA, Perlis, 2019)
Data plays an important role in the maintenance of collecting and processing huge amounts of information. The more data is stored, the more suitable and essential it is to ensure its safety. A lack of data security can result in great financial failures and reputational damage for any organization. Big data vulnerability comes when unauthorized person gains access to the data. Big data is a synthetic tools which gives us result. This paper displays various problems which are related to Big data problem and opportunity. Nevertheless, this paper suggests a BDS model or Big Data Security to provide the big data security. Just as companies start checking out e- Business activities such as sociable media for brand advertising and customer diamond, they have also started turning to data stats as well. Today, it is nearly impossible to find any brand that does not have sociable mass media presence. Looking at the growing of the data means the result of Big data issue will come. However, big data and digital evidences integrity require BDS model to provide the security of data in the organization.